Analisis Kerusakan dan Rekomendasi Konservasi pada Buku Menudju Kemerdekaan/Towards Independence Koleksi UPT Perpustakaan Proklamator Bung Hatta - Nisa, Nisa; Rahmah, Elva; Marlini, Marlini (TSAQOFAH, 2026)
This study aimed to analyze the types of damage and evaluate conservation practices applied to the rare book Menudju Kemerdekaan/Towards Independence, held in the collection of the Proklamator Bung Hatta Library Technical Implementation Unit (UPT), and to formulate appropriate conservation recommendations. As an important documentary source on the history of Indonesia’s struggle for independence, the book is highly vulnerable to material degradation due to age and environmental conditions. The research employed a qualitative method with a case study approach through direct observation of the book’s physical condition and in-depth interviews with the UPT conservator. The findings show that the book has suffered physical damage (loose binding, tears, and paper fragility), chemical damage (paper yellowing due to acidification), and biological damage (fungal attack). The curative conservation practices implemented by the UPT are considered fairly optimal and include mending with Japanese tissue, sterilization using 70% alcohol, and the application of collection preservation guidelines. However, conservation efforts are still constrained by limited facilities and infrastructure, particularly in environmental control, as temperature and humidity remain unstable due to insufficient air-conditioning coverage. Conservation recommendations include additional curative measures in the form of deacidification to address chemical deterioration, as well as binding repair using the portaple or book file method that does not alter the book’s original form. Preventively, the UPT needs to improve environmental control by adding dehumidifiers to slow down the rate of material degradation. This study underscores the urgency of early intervention in the preservation of written cultural heritage, in line with the principles emphasized by Shabrina and Yusniah (2025), to ensure the continuity of the nation’s intellectual legacy.